Recent methods for measuring dopamine D3 receptor occupancy in vivo: importance for drug development - Le Foll, Bernard; Wilson, Alan A.; Graff, Ariel; Boileau, Isabelle; Di Ciano, Patricia (Frontiers in Pharmacology, 2014)
There is considerable interest in developing highly selective dopamine D3 receptor ligands for a variety of mental health disorders. Dopamine D3 receptors have been implicated in Parkinson’s Disease, schizophrenia, anxiety, depression, and substance use disorders. The most concrete evidence suggests a role for the D3 receptor in drug-seeking behaviors. D3 receptors are a subtype of D2 receptors, and traditionally the functional role of these two receptors has been difficult to differentiate. Over the past 10-15 years a number of compounds selective for D3 over D2 receptors have been developed. However, translating these findings into clinical research has been difficult as many of these compounds cannot be used in humans. Therefore, the functional data involving the D3 receptor in drug addiction mostly comes from preclinical studies. Recently, with the advent of [11C]-(+)-PHNO, it has become possible to image D3 receptors in the human brain with increased selectivity and sensitivity. This is a significant innovation over traditional methods such as [11C]-raclopride that cannot differentiate between D2 and D3 receptors. The use of [11C]-(+)-PHNO will allow for further delineation of the role of D3 receptors. Here, we review recent evidence that the role of the D3 receptor has functional importance and is distinct from the role of the D2 receptor. We then introduce the utility of analyzing [11C]-(+)-PHNO binding by region of interest. This novel methodology can be used in preclinical and clinical approaches for the measurement of occupancy of both D3 and D2 receptors. Evidence that [11C]-(+)-PHNO can provide insights into the function of D3 receptors in addiction is also presented.